2001
DOI: 10.1198/016214501753381896
|View full text |Cite
|
Sign up to set email alerts
|

Matching With Doses in an Observational Study of a Media Campaign Against Drug Abuse

Abstract: Multivariate matching with doses of treatment differs from the treatment-control matching in three ways. First, pairs must not only balance covariates, but also must differ markedly in dose. Second, any two subjects may be paired, so that the matching is nonbipartite, and different algorithms are required. Finally, a propensity score with doses must be used in place of the conventional propensity score. We illustrate multivariate matching with doses using pilot data from a media campaign against drug abuse. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
180
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(180 citation statements)
references
References 32 publications
0
180
0
Order By: Relevance
“…This means that CEM works without modification for multicategory treatments: after the algorithm is applied, keep every stratum that contains all desired values of the treatment variable and discard the rest. This is a simple approach that can be easily used with or in place of more complicated approaches, such as based on generalizations of the propensity score (Imbens 2000;Lu et al 2001;Imai and van Dyk 2004).…”
Section: Multicategory Treatmentsmentioning
confidence: 99%
“…This means that CEM works without modification for multicategory treatments: after the algorithm is applied, keep every stratum that contains all desired values of the treatment variable and discard the rest. This is a simple approach that can be easily used with or in place of more complicated approaches, such as based on generalizations of the propensity score (Imbens 2000;Lu et al 2001;Imai and van Dyk 2004).…”
Section: Multicategory Treatmentsmentioning
confidence: 99%
“…This method uses a model such as an ordinal logit model to match on a linear combination of the covariates. This is illustrated in Lu, Zanutto, Hornik, and Rosenbaum (2001), where matching is used to form pairs that balance covariates but differ markedly in dose of treatment received. This differs from the standard matching setting in that there are not clear "treatment" and "control" groups, and thus any two subjects could conceivably be paired.…”
Section: Multiple Treatment Dosesmentioning
confidence: 99%
“…The causal e ect,ˆ t , is estimated using the matching estimator described in equation (5). The structure of the matches were 1 to 1 and only considered matches if close, e.g.…”
Section: Estimation Of Causal E Ectmentioning
confidence: 99%
“…Rosenbaum and Rubin [1] demonstrated that balancing on propensity scores removes bias due to all observed confounders. Only recently have propensity score methods been extended to multiple treatment settings [2][3][4][5][6]. While these extensions are promising, the choice of analytic model for the treatment assignment mechanism as well as its subsequent impact on the causal estimator remains unclear.…”
Section: Introductionmentioning
confidence: 99%